The Association of Parametrial Invasion with the Expression of Vascular Endothelial Growth Factor-C and Other Factors in Squamous Cell Cervical Carcinoma Stage IB and IIA - Lilis Lilis; Nurjati Chairani Siregar; Andrijono Andrijono (The Indonesian Biomedical Journal, 2019)
BACKGROUND: The presence of parametrial invasion in early stage squamous cell cervical cancer (SCCC) indeed indicates worse prognosis and need more adjuvant treatment. This study aimed to investigate the association between parametrial invasion and clinicohystopathology variables.METHODS: This retrospective study used specimens of squamous cell carcinoma stage IB-IIA. The inclusion criteria were cervical cancer stage IB-IIA and post radical hysterectomy with lymph node dissection and exclusion criteria was damaged and or insufficient histological preparations. The clinicohystopathology variables included age, tumour size and stage, differentiation and inflammation grade, lymphatic vascular and parametrial invasion, and lymph node metastasis. Histopathology staining, immunohistochemistry examination, and vascular endothelial growth factor-C (VEGF-C) expression were evaluated according to the standard procedure. The independent-T, Chi square, and Fisher’s exact test were applied to evaluate the association. The significance was set at p<0.05.RESULTS: Seventy-five cases were eligible. Parametrial invasion was found in 15 cases (20%). Three variables demonstrated a significant association with parametrial invasion, tumor size >4 cm (OR 4.32, 95% CI 1.29-14.38, p=0.01), lymphatic node metastasis (OR 3.90, 95% CI 1.17-13.03, p=0.02), and VEGF-C (OR 0.75, 95% CI 0.65- 0.87, p=0.03).CONCLUSION: Tumor size of >4 cm and lymph node metastasis (LNM) had a higher risk of parametrial invasion in SCCC stage IB-IIA.KEYWORDS: cervical carcinoma, parametrial invasion, vascular invasion, peritumoral stroma, VEGF-C expression